Semantic SEO: ISS Framework for content-intensive web sites optimization - Carlos Lopezosa (Cuadernos de Documentación Multimedia, 2018)
This article carries out a systematic review of the concept of semantic SEO and semantic searches, to configure a framework of work applied to content-intensive sites. It is intended to create a working procedure capable of helping to position web content in search engines in an enriched way (semantics). The main elements that characterize semantic SEO are theoretically reviewed: the knowledge graph, the hummingbird algorithm, the RankBrain, the LSI (latent Semantic Indexation), and the structured data. Next, the different semantic searches that are reproduced in Google's index are analyzed, and the Schema.org initiative is studied as the semantic marker standardized by the main search engines. Finally, these elements are configured as components of the Integral Framework of Semantic SEO (ISS).